Geocellular railway drainage systems: Physical and numerical modelling. (March 2020) - Tasalloti, Ali; Marshall, Alec M.; Heron, Charles M.; Hashemi, Mir Amid
Highlights: Full scale physical modelling of railway track considering geocellular units. Numerical modelling of unsaturated flow using Abaqus. Evaluation the effect of Permavoid on the hydraulic behaviour of railway track. Decrease in the steady-state water level, especially for cases with fouled ballast. Abstract: The importance of resilient railway infrastructure is paramount when considering the increased likelihood of extreme weather and flash flood events in coming years. One of the main causes of instability of railway tracks is excess water in the trackbed, particularly when it is at or above the interface of the ballast and subgrade. Conventional drainage systems are susceptible to clogging and deterioration. Resilient track drainage systems should therefore have sufficient capacity to allow water to dissipate quickly, but they should also be designed to ensure long-term operation with minimal or easily performed maintenance. This paper presents results from an investigation of a potential new railway drainage system using geocellular components. In the paper, the development of a large scale physical model is described which represents a full scale unit cell of a sleeper-to-sleeper track substructure. The physical model includes ballast and subgrade layers, under-track and lateral drainage systems, rainfall simulation, and instrumentation. Results demonstrate the relative hydraulic response of the drainage system with and without the geocellular components. The paper also describes the development of a numerical model of the track subgrade and drainage system, which was first calibrated and verified using experimental data from the physical model, then extended to study the effect of certain parameters on the hydraulic response of the railway track. Results indicate that the under-track geocellular drainage system offers potential benefits in terms of maintaining a lower water table level within the subgrade as well as in aiding the migration of fines out of the ballast.